The technology andragogy work content knowledge model framework on technical and vocational education and training - Zainal Arifin; Muhammad Nurtanto; Nur Kholifah; Soffan Nurhaji; Warju Warju (Journal of Education and Learning (EduLearn), 2020)
The main competence of 21st century technical and vocational education and training (TVET) teachers is the ability to integrate technology into the learning process effectively. However, the concept of learning is now shifting to technological involvement, learning approaches, and needs in accordance with the curriculum of the world of work must be integrated to produce learning outcomes that are able to compete in obtaining work opportunities. The technological pedagogical content knowledge (TPACK) model used in general learning needs to be assessed according to the context of innovation in the TVET learning field. The purpose of this study is to analyze the teaching and learning of TVET teachers who are professionals with the approach of Technology, Andragogy and Work towards Content Knowledge (CK). Study of qualitative methods in the form of document analysis is identified by the philosophy of the learning approach at TVET and the current TVET learning model. The analysis results recommend that the technology andragogy work content knowledge (TAWOCK) model is considered important to be developed in TVET learning. Characteristics of these findings include the involvement of learning using technology, increasing the level of learning for andragogy, adjusting work competence, and curriculum content developed on the concept of knowledge. Finally TPACK has been modified to TAWOCK to study in the TVET field.